Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Social Action Budget Brief - Mozambique 2021 - UNICEF and ILO (UNICEF and International Labour Organization (ILO), 2021)
Highlights The 2021 budget for social protection is worth MZN 10.1 billion. This represents a 50 percent nominal increase relative to the 2020 initial allocation (i.e. the first allocation approved by Parliament in 2020) before the onset of the COVID-19 pandemic. However, it represents a 2 percent nominal decrease relative to revised allocation (i.e. the allocation that was revised by Parliament in November 2020 in response to COVID-19), a 4 percent nominal decrease relative to updated allocation (i.e. funds that arrive at the disposal of social protection institutions), and a 26 percent nominal increase relative to the actual expenditure in 2020 (i.e. funds that were spent at the end of budget year) (see Glossary of budget terminology). It is important to highlight that 2020 revised allocation to the sector was exceptionally high as a result of financial support provided by international finance institutions and development partners to implement the sector’s response plan to COVID-19. While part of these funds appeared in the 2020 budget revision, they are de facto being executed in 2021 (i.e. when the actual transfers to beneficiaries of the Direct Social Support Programme - Post Emergency (PASD-PE) are taking place).
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; Social Protection PEA; budget / orçamento; social action / ação social; social protection / proteção social

A Pharmaceutical Logistics still far from answering health concerns of the country: budgetary weaknesses - N'weti (N'weti, 2020)
Key Messages: - Pharmaceutical logistics make up only 7% of total projected costs for the health sector through 2019; - The expansion and demand of the health sector in the forthcoming years will not be accompanied by the necessary increase in resources for the pharmaceutical logistics sector; - Increased nancing in the area of PL is necessary, preferably from internal sources, to allow the implementation of PELF recommendations; - It is estimated that 13% of the value of the approximately $3,929 million needed to procure and manage drugs and commodities during 2014-2019 will be wasted. - The health sector is heavily reliant on external funding, with 81% of funding for medicines comming from external partners; - There is concerning public evidence of systematic stock-outs of medicines in public pharmacies throughout the country. Research by Nweti (2014-2015) in 37 health acilities in four provinces using the community score card as a survey tool, found that stock-out of essential medicines was one of the barriers to accessing quality health services. Another study carried out by Wagenaar, et al. (2014) in Sofala Province, which assessed 26 facilities showed that only one out of the 26 facilities assessed in 2011, 2012, and 2013 had all of the 15 essential medicines.
Keywords: G - Mozambique / Moçambique; L - english / inglês; budget / orçamento; health / saúde